Two-Section Two-Zone Fluidized Bed Reactor fluid dynamics: experimental study, hydrodynamic modelling and CFD simulations - Julián, Ignacio; Herguido, Javier; Menéndez, Miguel (Jornada de Jóvenes Investigadores del I3A, 2014)
A Two Zone Fluidized Bed Reactor (TZFBR) represents an effective solution to integrate reaction and catalyst regeneration in a single fluidized bed reactor. Reactor hydrodynamics of an improved TZFBR configuration, that incorporates a different cross-sectional area between zones to allow a better fluid dynamic control on each zone separately, is here investigated.